The Failure of Hybrid Organizations: A Legitimation Perspective - Siwale, Juliana; Kimmitt, Jonathan; Amankwah-Amoah, Joseph (Management and organization review, 2021)
Organizational hybridity refers to the combination of multiple institutional logics and identities that, within an organizational setting, do not conventionally complement one another. In such conditions, organizations must develop strategies to combine logics and sustain their hybrid forms. Success, however, is not inevitable. In this article, we take a legitimacy-as-process perspective to focus on a failed Microfinance Organization (MFO) in the African context of Zambia. MFOs represent a fascinating context because of their hybrid nature and need to balance several competing institutional demands. We utilise field interviews to analyse the process through which MFOs fail, analysing actor legitimation responses to emerging hybridity demands. We identify three phases associated with these changes: 1) dependent coupling, (2) misaligning legitimation, and (3) circumnavigating over conformity. Our findings emphasise that legitimation efforts in a failed hybrid are not simply the reverse of those that succeed. We observe adaptive processes consistent with successful hybrids but that ultimately sow the seeds of eventual failure. This demonstrates the need to re-think the role of legitimation strategies in hybrids alongside their potential deleterious consequences.